A revision of the Australian species of the genus Melobasis Laporte & Gory 1837 (Coleoptera: Buprestidae), Part 2 (Revision of the nervosa species group) - Levey, Brian (Zootaxa, 2018)
This is the second part of a revision of the Australian members of the genus Melobasis Laporte & Gory 1837 and revises the species of the nervosa species group.13 new species and subspecies are described: M. angustecostata angustecostata ssp. n., M. angustecostata subacuta ssp. n., M. barkeri sp. n., M. brevimaculata sp. n., M. breviserrata sp. n., M. cupreovittata queenslandica ssp. n., M. cupreovittata westralica ssp. n., M. dissimilis sp. n., M. fortipunctata sp. n., M. latecostata sp. n., M. planithorax sp. n., M. soror basicostata ssp. n., M. vertebralis cuneata ssp. n. The following new synonymies are proposed: M. bicolor Blackburn is synonymised with M. rubromarginata Saunders; M. costata Thomson is synonymised with M. nervosa (Boisduval); M. semistriata Blackburn is synonymised with M. viridiceps Saunders; M. viridisterna Carter is synonymised with M. sordida Blackburn; M. victoriae Obenberger is synonymised with M. viridiceps Saunders. The following changes of status are proposed: M. costipennis Kerremans is removed from synonymy with M. lathami (Laporte & Gory); M. costata Thomson is removed from synonymy with M. interstitialis Blackburn; M. rubromarginata Saunders is removed from synonymy with M. lathami (Laporte & Gory); M. bicolor Blackburn is removed from synonymy with M. lathami (Laporte & Gory); M. sordida Blackburn is removed from synonymy with M. simplex Germar; M. soror Blackburn is removed from synonymy with M. lathami (Laporte & Gory).